Serial Changes in Intestinal Stenotic Stiffness in Patients with Crohn’s Disease Treated with Biologics: A Pilot Study Using Ultrasound Shear Wave Elastography - Matsumoto, Hiroshi; Hata, Jiro; Yo, Shogen; Sasahira, Momoyo; Misawa, Hiraku; Oosawa, Motoyasu; Handa, Osamu; Umegami, Eiji; Shiotani, Akiko (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Intestinal strictures represent an important serious complication of Crohn’s disease. Shear wave elastography is a promising noninvasive ultrasound technique for assessing tissue stiffness. This study aimed to evaluate stiffness in the areas of intestinal stricture in patients with Crohn’s disease using shear wave elastography and the changes in stiffness after biologics. Materials and Methods: We enrolled 21 Crohn’s disease patients having intestinal stricture. The patients consisted of 3 groups, which were the infliximab naïve (n = 6) group, the ustekinumab naïve (n = 8), and the bio-switch from infliximab to ustekinumab (n = 7) group. Bowell wall thickness was examined by ultrasound sonography, and the stiffness of Crohn’s disease stricture lesions was evaluated using Shear wave speed before and 1 year after anti-tumor necrosis factor-alpha antibody infliximab, anti-interleukin 12/23 antibody ustekinumab, and bio-switch from infliximab to ustekinumab. Results: Bowell wall thickness was significantly improved after infliximab, ustekinumab, and the bio-switch. However, shear wave speed indices only in the ustekinumab group significantly decreased after treatment (P = .028), but not in the other group. Conclusions: Shear wave elastography might be a useful method to evaluate stiffness in the areas of intestinal stricture in patients with Crohn’s disease treated with biologics. However, a prospective randomized study evaluating the development of obstruction after biological treatment is needed to validate the study findings.